Analysis of Lyrics Values Ebiet G. Ades Song as a Source of Character Education - Wibowo, Arif Sobirin; Harmanto, Harmanto; Jacky, M (The Indonesian Journal of Social Studies, 2019)
This research purpose to describe of lyrics values Ebiet G Ades song with the title for us to ponder as a source of character education values. This research uses a qualitative approach using Levi-Strauss structural analysis and Paul Ricoeur hermeneutics to find the ceritheme and episodes in every lyrics Ebiet G Ades song titled for us to ponder and later will be used as a source of character education values. The results of the research show that there are several character values in the lyrics Ebiet G Ades song that value is the character value in relation to God; Religious. Character values in relation to yourself; Hard Work, Discipline, Responsibility, Independent; Curiosity. Character values in relation to others; Friendly/ Communicative. Character values in relation to the environment; Care for the Environment, Care for Social.